PENGARUH KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Emilia Gustini (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of the study was to find out the effect of dividend and debt policies on corporate value. The population of the study were state-owned enterprisescompanieslistedin Indonesia Stock Exchange in 2012-2016. The sample consisted of 18 companies which was taken by using purposive sampling technique. In analyzing the data, multiple linear regression analysis was used in order to find out the effect of independent variable on the dependent variable either simultaneously or partially. The result of the analysis showed that in 2012-2016 the dividend policy was proxied by the dividend payout ratio (DPR) and the dividend yield (DY), the debt policy variable was proxied by the debt to equity ratio (DER) and the debt to asset ratio (DAR), and corporate value variable was proxied through price earning ratio (PER), simultaneously DPR, DY, DER, and DAR had significant effect on PER, whereas partially (1) DPR had a significant positive effect on PER. (2) DY had a significant negative effect on PER. (3) DER had a significant negative effect on PER, and (4) DAR had a significant positive effect on PER.Keywords: DPR, DY, DER, DAR, PER